Animal management practices in the Western Iberian Peninsula during the Neolithic-Chalcolithic transition: the study case of Leceia site (Oeiras, Portugal) - Navarrete, Vanessa (2023)
The principal aim of this work is to establish the degree of human control over the management and animal diet of domesticates and characterize different herding systems during the Neolithic-Chalcolithic transition in Leceia site.